Molecular biology of the cell - Alberts, Bruce; Morgan, David; Heald, Rebecca; Johnson, Alexander; Raff, Martin; Roberts, Keith; Walter, Peter (New York : W. W. Norton & Company, 2022)
"As the amount of information in biology expands dramatically, it becomes increasingly important for textbooks to distill this vast amount of scientific knowledge into concise principles and enduring concepts. Molecular Biology of the Cell, Seventh Edition accomplishes this goal with clear writing and beautiful illustrations. The Seventh Edition has been extensively revised and updated with the latest research in cell biology, and it provides an exceptional framework for teaching and learning. Molecular Biology of the Cell is widely used in introductory courses at the university level, being considered as a reference in many libraries and laboratories around the world. It describes the current understanding of cell biology and includes basic biochemistry, experimental methods for investigating cells, the properties common to most eukaryotic cells, the expression and transmission of genetic information, the internal organization of cells, and the behavior of cells in multicellular organisms. Molecular Biology of the Cell has been described as "the most influential cell biology textbook of its time""--
Cells and Genomes -- Cell Chemistry and Bioenergetics -- Proteins -- DNA, Chromosomes, and Genomes -- DNA Replication, Repair, and Recombination -- How Cells Read the Genome : From DNA to Protein -- Control of Gene Expression -- Analyzing Cells, Molecules, and Systems -- Visualizing Cells -- Membrane Structure -- Membrane Transport of Small Molecules and the Electrical Properties of Membranes -- Intracellular Compartments and Protein Sorting -- Intracellular Membrane Traffic -- Energy Conversion: Mitochondria and Chloroplasts -- Cell Signaling -- The Cytoskeleton -- The Cell Cycle -- Cell Death -- Cell Junctions and the Extracellular Matrix -- Cancer -- Development of Multicellular Organisms -- Stem Cells and Tissue Renewal -- Pathogens and Infection -- The Innate and Adaptive Immune Systems.
Includes bibliographical references and index.
MNS
Karim International
Keywords: Cells; Molecular Biology